Locating Organizations and Their Methods in Registrations of Clinical Migraine Trials: Analysis of ClinicalTrials.gov - Zhang, Pengfei; Do, Thien Phu (Frontiers in Neurology, 2021)
Background and Objective: ClinicalTrials.gov is a centralized venue for monitoring clinical research and allows access to information on publicly and privately funded studies. To better recognize influential institutions in in the field of headache, we identified major organizations conducting clinical trials in migraine research. Furthermore, we examined the frequency of different study designs. Methods: Utilizing the ClinicalTrials.gov application programming interface, we extracted studies including individuals with migraine from February 29, 2000 to July 28, 2020 for the following: (1) host organization; (2) study type; (3) primary purpose; (4) intervention model; (5) allocation. Results: We included 921 entries encompassing 423 organizations. Thirty-two organizations produced ≥5 entries each and 40.0% of all entries. Most, 86%, were interventional studies while 13.6% were observational studies. The most common study design had a randomized allocation of participants. The most frequent primary purpose was treatment (62.4%) followed by prevention (13.0%). There were 56.9% parallel assignment models, 15.2% single group assignment models, and 12.4% crossover assignment models. Conclusion: A minority of organizations contribute to a significant number of registrations of clinical migraine trials suggesting that clinical research in migraine is oligarchic. The most common study is interventional, randomized, with parallel assignment of participants with treatment as the primary purpose. This likely reflects the need to evaluate novel putative pharmacological medications.